2014
DOI: 10.11648/j.sjac.20140205.11
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-Friendly Method for Extraction and Determination of Ciprofloxacin in Blood Serum and Pharmaceuticals

Abstract: A method was established for the determination of ciprofloxacin hydrochloride (CIPRO) in the blood serum and pharmaceutical samples by a combination of cloud point extraction with UV-Vis spectrophotometry. The method included the formation of Fe (III) -CIPRO complex in presence of dilute H 2 SO 4 , followed the extraction of the complex by cloud point extraction using non-ionic surfactant Triton X-114. The surfactant phase extracted was dissolved in little amount of solvent and the CIPRO quantity measured spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…depends on the nature of the metabolism between each volunteer) or to how discharge medication by the body; is that the remaining drug distracted by the kidneys. As it, this is the reason that there is a difference in the proportion of drug in the blood because of the difference in kidney function among the volunteers 21 . The developed method was also applied for the detection of NOR content in one of the selected pharmaceutical preparation containing NOR such as Norflox (eye drop) with stated value of 0.3%.…”
Section: Determination Of Nor In Serum Samples and Pharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…depends on the nature of the metabolism between each volunteer) or to how discharge medication by the body; is that the remaining drug distracted by the kidneys. As it, this is the reason that there is a difference in the proportion of drug in the blood because of the difference in kidney function among the volunteers 21 . The developed method was also applied for the detection of NOR content in one of the selected pharmaceutical preparation containing NOR such as Norflox (eye drop) with stated value of 0.3%.…”
Section: Determination Of Nor In Serum Samples and Pharmaceuticalsmentioning
confidence: 99%
“…However, there are only two papers appeared in literature concerning the determination of NOR by using HPLC in complex matrices such as human serum 20 and milk products. Although HPLC has a good detection power, but it does not exist in most laboratories, need an internal standard and sometimes involve more than one extraction step 21 . It was reported that the use of molecular spectrophotometry combined with cloud point extraction (CPE) provides attractive features which drive toward simplification and facilitation of the analytical procedures in routine analyses of organics and metal ions in different matrices instead of using sophisticated and expensive instrumentations 22,23 .…”
Section: Research Articlementioning
confidence: 99%
“…40 , and spectrophotometry 41,42,43 . Although HPLC has good analytical potential for determination of norfloxacin, but most laboratories lack in facilitating such sophisticated techniques 44 . Spectrophotometric methods are simpler in routine analyses of organics and metal ions in different matrices instead of using sophisticated and expensive instrumentations.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Although these techniques are sophisticated and have a high detection power but they are relatively expensive and not always available in all laboratories. Recently, the combination of UV-Vis spectrophotometry with cloud point extraction (CPE) has proved to offer a promising alternative method of improving conventional analytical procedure toward easy, simple, eco-friendly and inexpensive routine analyses of the pharmaceuticals in different matrices instead of using expensive instrumentations [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%